Opportunities and challenges to implementing mRNA-based vaccines and medicines: lessons from COVID-19 - Iqbal, Shehzad M.; Rosen, Andrew M.; Edwards, Darin; Bolio, Ana; Larson, Heidi J.; Servin, Mariana; Rudowitz, Marcy; Carfi, Andrea; Ceddia, Francesca (Frontiers in Public Health, 2024)
The messenger RNA (mRNA) platform emerged at the forefront of vaccine development during the COVID-19 pandemic, with two mRNA COVID-19 vaccines being among the first authorized globally. These vaccines were developed rapidly informed by decades of laboratory research, and proved to be safe and efficacious tools for mitigating the global impact of the COVID-19 pandemic. The mRNA platform holds promise for a broader medical application beyond COVID-19. Herein, we provide an overview of this platform and describe lessons learned from the COVID-19 pandemic to help formulate strategies toward enhancing uptake of future mRNA-based interventions. We identify several strategies as vital for acceptance of an expanding array of mRNA-based vaccines and therapeutics, including education, accurate and transparent information sharing, targeted engagement campaigns, continued investment in vaccine safety surveillance, inclusion of diverse participant pools in clinical trials, and addressing deep-rooted inequalities in access to healthcare. We present findings from the Global Listening Project (GLP) initiative, which draws on quantitative and qualitative approaches to capture perceptions and experiences during the COVID-19 pandemic to help design concrete action plans for improving societal preparedness for future emergencies. The GLP survey (>70,000 respondents in 70 countries) revealed tremendous disparities across countries and sociodemographic groups regarding willingness to accept novel mRNA vaccines and medicines. The comfort in innovations in mRNA medicines was generally low (35%) and was marginally lower among women (33%).The GLP survey and lessons learnt from the COVID-19 pandemic provide actionable insights into designing effective strategies to enhance uptake of future mRNA-based medicines.